2019
DOI: 10.1152/ajpregu.00370.2018
|View full text |Cite
|
Sign up to set email alerts
|

Cold acclimation triggers lipidomic and metabolic adjustments in the spotted wing drosophilaDrosophila suzukii(Matsumara)

Abstract: Chronic cold exposure is detrimental to chill susceptible insects that may accumulate chill injuries. To cope with deleterious effects of cold temperature, insects employ a variety of physiological strategies and metabolic adjustments, such as production of cryoprotectants, or remodeling of cellular membranes. Cold tolerance is a key element determining the fundamental niche of species. Because Drosophila suzukii is an invasive fruit pest, originating from East Asia, knowledge about its thermal biology is urge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 109 publications
(184 reference statements)
0
24
0
Order By: Relevance
“…Cellular ion homeostasis, although also crucial for ensuring the function of neuronal signal transduction and muscle contraction (Lubawy et al, 2020; MacMillan et al, 2014; Pivovarov et al, 2019), was not associated with gene family expansions in N. riversi . Similarly, changes to the structure of the phospholipid bilayer, which is a common strategy to avoid damage to the cytoplasmic membrane and internal membranes (Enriquez & Colinet, 2019; Holmstrup et al, 2002), was not found among the gene expansion events. There are three possible reasons we do not find evidence for these physiological changes.…”
Section: Discussionmentioning
confidence: 99%
“…Cellular ion homeostasis, although also crucial for ensuring the function of neuronal signal transduction and muscle contraction (Lubawy et al, 2020; MacMillan et al, 2014; Pivovarov et al, 2019), was not associated with gene family expansions in N. riversi . Similarly, changes to the structure of the phospholipid bilayer, which is a common strategy to avoid damage to the cytoplasmic membrane and internal membranes (Enriquez & Colinet, 2019; Holmstrup et al, 2002), was not found among the gene expansion events. There are three possible reasons we do not find evidence for these physiological changes.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that the properties of the insect cuticle may be determined by the complex structural interactions between chitin polysaccharides and cuticular proteins (CPs) [29]. Moreover, extreme cold environment can affect cellular membrane integrity by inducing the transition of membrane's phospholipid bilayer [30]. These changes in membrane fluidity alter function and activity of membrane-bound enzyme [31,32].…”
Section: Introductionmentioning
confidence: 99%
“…And there has little changed in their state, organ development, and tissue differentiation [35]. However, their physiological metabolic processes are still active, such as energy metabolism, endocrine regulation, lipid metabolism and sugar metabolism [30,36,37]. In energy metabolism, it has been proved that lowmolecular-weight sugars and polyols are vital intermediate metabolites and energy substances in many insect species in a cold environment [18].…”
Section: Introductionmentioning
confidence: 99%
“…Cold acclimation is a potential strategy to allow adaptation to cold environments and it attenuates cold-induced impairments [4]. Prolonged or intermittent repeated exposure to low temperatures is a way to improve cold acclimation and enhance the ability of cold adaptation [2,5,6]. However, the therapeutic strategy to increase the ability of cold adaptation is still less studied.…”
Section: Introductionmentioning
confidence: 99%